Refining maritime boundary delimitation methodology: the search for predictability and certainty - Hamid, Abdul Ghafur@Khin Maung Sein (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2019)
By virtue of the sole reliance on equitable principles, in total disregard of the equidistance method, in the North Sea Continental Shelf cases and vague and hollow provisions of United Nations Convention on the Law of the Sea (UNCLOS) 1982 in particular on the delimitation of the exclusive economic zone and the continental shelf, the maritime boundary delimitation methodology remained uncertain and confusing for decades. The main objective of the present paper is to investigate how the delimitation methodology could be refined to be more predictable and certain through the flexible interpretation of the conventional law by the decisions of international courts and tribunals. The paper first of all traces the codification history of the UNCLOS 1982 in order to ascertain the view of States expressed during the drafting process, which reflected the bitter rivalry between the two camps of equidistance and equitable. The paper then makes a painstaking analysis of the decisions of international courts and tribunals since 1990s to the most recent one and finds that the equidistance principle has been reinstated as a basic methodology in maritime boundary delimitation, supplemented by relevance circumstances, in order to achieve an equitable solution. The paper concludes that the search for predictability and certainty in maritime boundary delimitation has to some extent been achieved in the form of the recent three-stage approach, although there are still grey areas where significant uncertainty remains.